Review Potensi Biomassa Cangkang Kemiri (Aleurites moluccana) Sebagai Bahan Baku Karbon Aktif Penyerap Merkuri - Eka Marya Mistar; Rita Sunatarty; Ikramullah Zein; Maulinda Maulinda; Chairul Amni (Fakultas Teknik, 2023)
AbstractActivated carbon derived from biomass as an adsorbent has attracted much interest due to its environmentally friendly nature, abundant and porous structure. This paper aims to summarize literature studies of activated carbon generated from candlenut shells (Aleurites moluccana) via a chemical was activation process. The availability of these raw materials is very abundant in Indonesia that requires serious attentions to reduce the accumulation of solid waste which cause the environmental problems. One possible solution is that the biomass can be converted to an adsorbent which can absorb the heavy metal that can damage the environment. The results of previous studies indicate that activated carbon produced from candlenut shells could effectively absorbs mercury.Keywords : activated carbon, candlenut shell, biomass, adsorbent, mercury